Occurrence of Ips duplicatus (Coleoptera: Curculionidae, Scolytinae) on pines (Pinus sp.) in the Czech Republic and southern Poland - Short Communication - J. Holuša; W. Grodzki (Journal of Forest Science, 2008)
Spruce is regarded as the only host plant of Ips duplicatus in Central Europe, whereas this beetle exceptionally occurs on pine in Siberia. Its occurrence on Pinus strobes and Pinus sylvestris was discovered in the eastern part of the Czech Republic and in southern Poland, where the population density of Ips duplicatus has been increased for a long time on Norway spruce. However, all cases concerned only single trees which were growing in forest complexes with spruce dominance. The most likely explanation is merely a consequence of the typical host plant shortage.